(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This action research aimed to improve reading comprehension among second-grade students at SMAN 1 Pangkalan Kuras by implementing the Peer-Assisted Learning Strategy (PALS). The study combined professional development with experimental classroom research. Each cycle involved planning, action, observation, and reflection. Data were collected through tests, observation, field notes, and interviews. Quantitative analysis of test scores showed improvements in reading comprehension. Qualitative analysis of observation and interview data highlighted increased student engagement and motivation. The findings from classroom action research conducted at SMAN 1 Pangkalan Kuras demonstrate the effectiveness of implementing the Peer Assisted Learning Strategy (PALS) in enhancing senior high school students’ reading comprehension skills. Through PALS, students engaged actively in collaborative learning, which led to deeper understanding of texts and increased motivation to participate in learning activities. The study revealed significant improvements in student participation and academic achievement in narrative comprehension, highlighting the potential of PALS to enhance English language learning outcomes in high school settings.